Generation Planning Methodology Based on Load Factor for Hydroelectric Power Plants - Sevilgen, Suleyman Hakan; Erdem, Hasan Huseyin (HINDAWI PUBLISHING CORPORATION, 2014)
Major parameters affecting the generation capacity of hydroelectric plants are resource regime, reservoir geometry, and water head together with flow rate and efficiency. For the same resource regime and flow rate, water head can be altered depending on generation planning. By means of holding water in the reservoir and consequent increase in head can lead to boost power generation. In this paper, a method to compare two different operational styles has been identified; a plant operating with a low fixed head has been compared to a plant with an increased water head by means of holding water. In order to achieve this objective, an economical model including annual power revenues and net income increase depending on the operational strategy has been developed. Parameters affecting net income gain of the developed model are power generation boost and loss during peak and nonpeak durations, and electricity prices during peak and nonpeak durations. Depending on this model, strategies that would increase the plant revenue streams with increasing reservoir head have been presented in the results section of the paper.
Keywords: HYDRO; OPTIMIZATION; OPERATION; Thermodynamics; Engineering